Growth characteristics of maize seeds exposed to magnetic field. Issue 2 (17th November 2016) - Vashisth, Ananta; Joshi, Devendra Kumar
Abstract : Standardization of magnetic field was done for maximum enhancement in germination characteristics of maize seeds. Seeds of maize were exposed to static magnetic fields of strength 50, 100, 150, 200, and 250 for 1, 2, 3, and 4 h for all field strengths. Results indicate that magnetic field application enhanced seed performance in terms of percentage germination, speed of germination, seedling length, and seedling dry weight significantly compared to unexposed control. Among the various combinations of field strength and duration, 200 mT for 1 h exposure gave best results. Exposure of seeds to magnetic fields improved seed coat membrane integrity as it reduced cellular leakage and, consequently, electrical conductivity. Experiments conducted at a research farm as well as farmer's field showed that plants raised from seeds exposed to 200 mT for 1 h had higher values of leaf area index, shoot length, number of leaves, chlorophyll content, shoot/root dry weight, and root characteristics as compared to corresponding values in untreated control. From the studies, it may be concluded that exposure of dry seeds to static magnetic field of 200 mT for 1 h improved shoot and root growth. Improved root system and biomass led to increased seed yield. Improved functional root parameters suggested that magnetically treated maize seeds could be used under moisture stress conditions. Bioelectromagnetics. 38:151–157, 2017. © 2016 Wiley Periodicals, Inc.